EFFECT OF INFRASTRUCTURE DEVELOPMENT ON THE EXPANSION OF TOURISM BUSINESSES IN AGODI GARDENS IBADAN OYO STATE, NIGERIA - Samuel Taiwo OLABOSINDE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study investigates how infrastructure development influences the expansion of tourism businesses in Nigeria using several regression analyses on data from 270 respondents. The study found that the security infrastructure positively and significantly influences the increase in tourism, with a coefficient of 0.496 and a t-value of 5.794 (p = 0.000). The communication infrastructure showed a negative influence with a coefficient of -0.275 and a t-value of -3.309 (p = 0.001). Utility infrastructure equally negatively affected tourism growth with a coefficient of -0. 201 and a t-value of -3.064 (p = 0.002). Furthermore, the study found a negative correlation between utility infrastructure and tourism growth, with a coefficient of -0.110 and a t-value of -2.252 (p = 0.032). The study ends with several suggestions: investing in better security infrastructure to increase safety, modernising communication systems to improve accessibility, addressing utility shortcomings by guaranteeing consistent energy and water supply, and strengthening financial infrastructure by improving credit access and reducing interest rates. These recommendations attempt to fix the infrastructure problems, thereby promoting the expansion of Nigerian travel agencies.